1986
DOI: 10.1093/nar/14.20.8209
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the murine IgH enhancer: evidence for negative control of cell-type specificity

Abstract: We have carried out a mutational analysis of the mouse IgH enhancer. Consistent with previous reports, deletions extending from either the 5' side or the 3' side of the enhancer fail to reveal distinct boundaries which define enhancer function in lymphoid cells. Interestingly, internal point mutations and deletions within the "enhancer core" regions fail to identify any necessary functional role for these conserved elements. When tested in CV1 cells, which do not normally respond to the IgH enhancer, certain d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 33 publications
5
82
1
Order By: Relevance
“…In fact when the O site, in con junction with (xE4, is repeated tandemly, it can function as a tissue-specific enhancer (Gerster et al 1987). Fi nally, the sequences flanking the core enhancer are im portant for enhancer repression in inappropriate cells; deletion of these sequences allows the enhancer to func tion in fibroblasts (Imler et al 1987) or kidney cells (Kadesch et al 1986), or in T cells and macrophages as re ported here, even with a wild-type O site. Apparently negative regulation is dominant to the positive-enhancer elements, as fusion of B cells with non-B cells extin guishes enhancer-activated transcription (Junker et al 1988;Zaller et al 1988).…”
Section: Ig Heavy-chain Enhancer Regulationmentioning
confidence: 68%
See 1 more Smart Citation
“…In fact when the O site, in con junction with (xE4, is repeated tandemly, it can function as a tissue-specific enhancer (Gerster et al 1987). Fi nally, the sequences flanking the core enhancer are im portant for enhancer repression in inappropriate cells; deletion of these sequences allows the enhancer to func tion in fibroblasts (Imler et al 1987) or kidney cells (Kadesch et al 1986), or in T cells and macrophages as re ported here, even with a wild-type O site. Apparently negative regulation is dominant to the positive-enhancer elements, as fusion of B cells with non-B cells extin guishes enhancer-activated transcription (Junker et al 1988;Zaller et al 1988).…”
Section: Ig Heavy-chain Enhancer Regulationmentioning
confidence: 68%
“…Recently, evidence for the negative regulation of the heavy-chain enhancer has been presented (Kadesch et al 1986;Wasylyk and Wasylyk 1986). Indeed, experiments using deletion mutants within the enhancer suggest that tissue specificity is, at least in part, mediated by se quences that flank the core enhancer and that act to re press enhancer function, that is, removal of these flanking sequences allows enhancer-mediated gene ex pression in fibroblasts (Imler et al 1987).…”
mentioning
confidence: 99%
“…For example, the E-boxes in the IgH enhancer are nearly identical to the E-boxes in the muscle creatine kinase enhancer, and Myod binds with equally high affinity to both sets of E-boxes in gel shift assays (Kadesch et al, 1986). In addition, Myod can bind and activate the expression of reporter constructs driven by the IgH E-boxes in transient transfection assays.…”
Section: Myod and Chromatin Remodelingmentioning
confidence: 99%
“…The enhancer contains three elements homologous to the core element identified by mutational analysis of the SV40 enhancer, and this footprint maps to the region of the most downstream core site. Previous mutational analysis concluded that these core sites were not required for B cell-specific activity of the enhancer suggesting that PU.1 binding to this site may represent a nonfunctional interaction (35).…”
Section: Analysis Of Mutation M103-mentioning
confidence: 99%